THE IMPACT OF THE GREEN MARKETING MIX ON THE PURCHASING DECISIONS ABOUT LE MINERALE - Putri, Yulia Hamdaini; Nasution, Syahrial Sabari; Maulana, Ahmad (Distribusi - Journal of Management and Business, 2025)
Global awareness of environmental issues has encouraged companies to adopt sustainability-oriented marketing strategies, known as green marketing. This study examines the influence of the green marketing mix on consumer purchasing decisions for Le Minerale bottled water products at Sriwijaya University. Using a quantitative method with 90 respondents, the research found that the green product and green place dimensions significantly influence purchasing decisions, while green price and green promotion do not. However, all four dimensions simultaneously have a significant influence on purchasing decisions, indicating that a comprehensive implementation of green marketing strategies can increase consumer trust and encourage more environmentally conscious purchases. Although limited to one brand and region, this study affirms the important role of green marketing as an effective strategy for companies committed to sustainability.